Pengaruh Premi Asuransi, Claim dan Recovery Terhadap Kualitas Layanan Melalui Kepuasan Pengguna Asuransi Kendaraan Bermotor di Kota Makassar - Herlina,; Ramlawati,; Suriyanti, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Insurance is a financial means in economic guarantees, both in facing risks to owned assets. This study aims to analyze the direct and indirect effects of insurance premiums, claims and recovery on service quality through motor vehicle insurance user satisfaction. This study uses a quantitative method approach. The data collection technique (instrument) used is a survey and questionnaire. The population and sample are purposive motor vehicle insurance users totaling 126 respondents. Data analysis uses SEM-PLS analysis with outer and inner models. The results of the study found that insurance premiums and claims directly have a positive and significant effect on the quality of motor vehicle insurance services. Recovery has a positive and insignificant effect on the quality of motor vehicle insurance services. Insurance premiums, claims and recovery directly have a positive and significant effect on the satisfaction of motor vehicle insurance users. User satisfaction directly has a positive and significant effect on the quality of motor vehicle insurance services. Insurance premiums, claims and recovery directly have a positive and significant effect on service quality through motor vehicle insurance user satisfaction in Makassar City.